Τι λένε οι χρήστες - Σύνταξη κριτικής
Δεν εντοπίσαμε κριτικές στις συνήθεις τοποθεσίες.
Άλλες εκδόσεις - Προβολή όλων
added addition affected algebraic arithmetical binomial called cents changed coefficient common denominator complete consequently consisting containing cube root Define denominator denote Divide dividend division equa equal equation equivalent EXAMPLES Explain the operation exponent expression factors figures find the values formulas four fourth fraction geometrical Given gives greatest common divisor Hence indicated known last term less letter manner means method miles Multiply negative Note number of terms obtain perfect person polynomial positive pounds progression proportion quadratic equation quan quotient radical Raise ratio Reduce remainder Repeat the Rule represent Required Resolve result second operation similar simple solved square root Substituting subtraction taken Theorem third tion tity transposing twice units unknown quantity values of x Whence whole write
Σελίδα 55 - That is, the square of the sum of two quantities is equal to the square of the first, plus twice the product of the first by the second, plus the square of the second.
Σελίδα 305 - ... that is, Any term of a geometric series is equal to the product of the first term, by the ratio raised to a power, whose exponent is one less than the number of terms. EXAMPLES. 1.
Σελίδα 294 - ... two triangles are to each other as the products of their bases by their altitudes.
Σελίδα 56 - The square of the difference of two quantities is equal to the square of the first minus twice the product of the first by the second, plus the square of the second.
Σελίδα 281 - ... if the circumference of each wheel be increased one yard, it will make only 4 revolutions more than the hind wheel, in the same distance ; required the circumference of each wheel.
Σελίδα 176 - In each succeeding term the coefficient is found by multiplying the coefficient of the preceding term by the exponent of a in that term, and dividing by the number of the preceding term.
Σελίδα 53 - Divide the first term of the dividend by the first term of the divisor, and write the result as the first term of the quotient. Multiply the whole divisor by the first term of the quotient, and subtract the product from the dividend.
Σελίδα 46 - The exponent of a letter in the quotient is equal to its exponent in the dividend, minus its exponent in the divisor. 439. Let it be required to divide a* by a1.